Pregnancy stressors and postpartum symptoms of depression and anxiety: the moderating role of a cognitive–behavioural therapy (CBT) intervention - Ahmed Zaidi; Atif Rahman; Pamela J Surkan; Najia Atif; Abid Malik; Yunxiang Sun; Soim Park (General Psychiatry)
Background Little is known about the association between stressors (especially positive stressors) during pregnancy and postpartum depression and anxiety.Aims We investigated the association between positive and negative stress events during different stages of pregnancy and postpartum mental health outcomes among low-income pregnant women with symptoms of anxiety in Pakistan and evaluated whether an intervention based on cognitive–behavioural therapy (CBT) had a regulatory effect.Methods Participants were 621 pregnant Pakistani women with mild anxiety. Using the Pregnancy Experience Scale-Brief Version, six scores were created to assess positive and negative stressors. We performed a multivariate linear regression to examine whether these six scores, measured both at baseline and in the third trimester, were associated with postpartum anxiety and depressive symptoms. The effect of the intervention on this relationship was examined by adding an interaction term to the regression model.Results Hassles frequency measured in the third trimester was positively associated with depression (B=0.22, 95% confidence interval (CI): 0.09 to 0.36) and anxiety (B=0.19, 95% CI: 0.08to 0.30). At the same timepoint, uplifts intensity was negatively associated with symptoms of depression (B=−0.82, 95% CI: −1.46 to –0.18) and anxiety (B=−0.70, 95% CI: −1.25 to –0.15), whereas hassles intensity was positively related to symptoms of depression (B=1.02, 95% CI: 0.36 to 1.67) and anxiety (B=0.90, 95% CI: 0.34 to 1.47). The intensity ratio of hassles to uplifts reported in the third trimester was positively related to both depression (B=1.40, 95% CI: 0.59 to 2.20) and anxiety (B=1.26, 95% CI: 0.57 to 1.96). The intervention strengthened the overall positive effects of uplifts and the negative effects of hassles. Pregnancy experiences at baseline during early pregnancy to mid-pregnancy were not associated with mental health outcomes.Conclusions Stressors in the third trimester but not earlier in pregnancy were associated with postpartum symptoms of anxiety and depression. The CBT intervention modified the association between pregnancy stressors and postpartum mental health outcomes. Programmes that promote positive experiences and reduce negative experiences, especially in late pregnancy, may mitigate postpartum mental health consequences.Trial registration number NCT03880032.